MEASURING BABY’S BODY LENGTH UTILIZING IMAGE PROCESSING - Windy Andhika Putra; Muhammad Rizqy Alfarisi; Gita Indah Hapsari; Periyadi (Fakultas Teknik Universitas Lambung Mangkurat, 2022)
The Baby Body Length Measurement System with Machine Learning methods and Open CV library is a system designed to make it easier for Posyandu officers to take measurements of the baby's body length, where this system will measure the baby's body length using a camera, and assisted with library image processing, namely, Open CV, and to measure the length of the baby's body using Machine Learning, namely the Linear Regression method, and the measurement data will be sent to a Web application so that the baby's mother can monitor the growth and development of her baby, The system that was built has an average error of -1,42 in the condition of the lamp with a power of 40Watt and in the light of a lamp with a power of 11Watt the average error is found with a value of -15,37 and at a distance of 64 cm the system can detect objects and measure the length of the object with an average measurement error of -10,6.